Materialien zur Documenta IX : Ein Reader für Unterricht und Studium. - Ammann, Jean-Christophe; Arndt, Matthias; Baum, Klaus; Blotkamp, Carel; Bromig, Christian; Böcker, Barbara; Eucker, Johannes; Faust, Wolfgang Max; Grauer, Michael; Hahn, Werner; Haustein, Lydia; Heller, Markus; et al. (Kassel : Edition Cantz., 1992)
Abramovic, Marina ; Absalon ; Artschwager, Richard ; Bacon, Francis ; Bagnoli, Marco ; Baikas, Nicos ; Balka, Miroslaw ; Barney, Matthew ; Barr, Jerry ; Baumgarten, Lothar ; Bertrand, Jean-Pierre ; Biberstein, Michael ; Bijl, Guillaume ; Birnbaum, Dara ; Borofsky, Jonathan ; Bourgeois, Louise ; Brandl, Herbert ; Brey, Ricardo ; Brown, Tony ; Burki, Marie José ; Bustamante, Jean-Marc ; Buthe, Michael ; Cabrita Reis, Pedro ; Caldas, Waltercio ; Calzolari, Pierpaolo ; Caramelle, Ernst ; Carroll, Lawrence ; Cemin, Saint Clair ; Ciecierski, Tomasz ; Clark, Tony ; Coleman, James ; Conrad, Tony ; de Cordier, Thierry ; Corillon, Patrick ; Damian, Horia ; Deacon, Richard ; Defraoui, Silvie & Cherif ; Delvoye, Wim ; Dimitrijevic, Braco ; Dittborn, Eugenio ; Dorner, Helmut ; Douglas, Stan ; Dumas, Marlene ; Durham, Jimmie ; Edoga, Mo ; Fabre, Jan ; Fabro, Luciano ; Fainaru, Belu-Simion ; Fend, Peter ; Finn-Kelcey, Rose ; Flatz ; Förg, Gunther ; Fortuyn/O'Brien ; François, Michel ; Frandsen, Erik A. ; Frenkel, Vera ; Funakoshi, Katsura ; Genzken, Isa ; Gerber, Gaylen ; Gober, Robert ; Graham, Dan ; Graham, Rodney ; Grauerholz, Angela ; Gross, Michael ; Hadjimichalis, George ; Hammons, David ; Herold, Georg ; Hill, Gary ; Hopkins, Peter ; Horn, Rebecca ; Horn, Roni ; James, Geoffrey ; Jenssen, Olav Christopher ; Johnson, Tim ; Kabakov, Ilya ; Kapoor, Anish ; Katase, Kazuo ; Kawamata, Tadashi ; Kelley, Mike ; Kelly, Ellsworth ; De Keyser, Raoul ; Khakhar, Bhupen ; Kippenberger, Martin ; Kirkeby, Per ; Klingelhöller, Harald ; Kocherscheidt, Kurt ; Kogler, Peter ; Kokolia, Vladimir ; Kosuth, Joseph ; Kruk, Mariusz ; Kuitca, Guillermo ; Lafont, Suzanne ; Lange, Gustav ; Lasker, Jonathan ; Leirner, Jac ; Leonard, Zoe ; Leroy, Eugène ; Lewandowsky, Via ; Lohaus, Bernd ; etc.
Duits
boek